Rancang Bangun Mesin Pencacah Rumput dan Pelepah Kelapa Sawit dengan Penggerak Motor Bensin Sebagai Pakan Ternak - Hasbi Assiddiq S; Asrul; Pratama Hermanto (P3M Politeknik Negeri Cilacap, 2022)
In increasing cattle productivity by using the cage method, adequate feed availability is needed. Farmers in Mandala Village still use the traditional method of chopping feed during the process of providing feed, which requires a lot of energy and time. The purpose of this research is to make a chopping machine for animal feed and to find out the results of the machine chopping. The method used is observation, literature review, experimental method, and design method. The grass chopper machine as a result of the research has a chopping chamber size of 360 x 360 x 490 mm, blade 270 x 50 x 10 mm, with a gasoline motor drive of 5,5 HP, transmission pulley, and V-belt type A-45. The chopping results obtained were 5,75 kg of palm fronds and leaves, 19,25 kg of trees and banana leaves, and 5 kg of grass in the chopping time of 02.00 minutes each at an average engine speed of 2100 rpm with the size of the chopped results between 3-6 cm